Actually in Nordic tweets. Issue 4 (14th May 2021) - Tyrkkö, Jukka; Levin, Magnus; Laitinen, Mikko
Abstract: 'Native‐like' use of discourse markers is a good indicator of language proficiency. Analysing four subcorpora of English‐language tweets posted by Twitter users from the Nordic countries of Finland, Norway, and Sweden, this study considers the effects of discursive context and L1 influence on the correlation between semantic function and sentence position of the discourse marker actually . The study shows that both predictors appear to have a significant effect. A more formal context predicts more standard punctuation, distribution of the pragmatic functions, and placement of the discourse marker, and L1 influence is reflected in the preferred sentence position, with a substantial and significant difference observed between the Finnic and Germanic L1s. Furthermore, the study shows that while the discourse marker actually is significantly more frequent in colloquial Twitter language than in spoken English, the frequency is significantly lower and in line with spoken English in more constrained contexts.